Communication and the Monitoring, Analysis, Evaluation, and Control of Risk as Predictors of Clinical Risk Management Implementation - Ahmad, Fadli; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Clinical Risk Management (CRM) is a systematic approach to identifying, analyzing, evaluating, and controlling risks to improve the quality and safety of patient care in hospitals. This study aimed to analyze the factors associated with the implementation of CRM at Pertamina Hospital Pangkalan Brandan, particularly in terms of organizational systems, leadership, culture, training, communication, and risk control. This study used a quantitative approach with a cross-sectional design. The sample consisted of 180 healthcare workers at Pertamina Hospital Pangkalan Brandan. Data were collected using a structured questionnaire and analyzed using multiple logistic regression tests to identify the dominant factors influencing CRM implementation. Bivariate analysis indicated that all independent variables; organizational systems (p = 0.000), leadership (p = 0.000), cultural understanding (p = 0.000), training (p = 0.000), communication (p = 0.000), and monitoring, analysis, evaluation, and risk control (p = 0.000) were significantly associated with CRM. Multivariate analysis revealed that the most influential variables in CRM implementation were communication (OR = 18.991) and monitoring, analysis, evaluation, and risk control (OR = 56.403). As conclusion, the dominant predictors of the implementation of CRM at Pertamina Hospital, Pangkalan Brandan are communication and the monitoring, analysis, evaluation, and control of risk.Keywords: clinical risk management; communication; risk control; hospital; service quality